(In)Animate Semiotics: Virtuality and Deleuzian Illusion(s) of Life. (March 2019) - Roberts, Spencer
It is well known that, despite his close engagement with cinema, Gilles Deleuze was less concerned with animated film, being somewhat dismissive of its capabilities. In recent years, however, a number of attempts have been made – most notably by William Schaffer, Thomas Lamarre and Dan Torre – to construct Deleuzian positions in animation theory. This article outlines some of these approaches, whilst engaging critically with Torre's writings. In particular, it foregrounds Torre's neglect of the post-structural, political dimension of Deleuzian thought through an examination of the concepts of faciality, the close-up, and relation as they occur in Deleuzian and Deleuzo-Guattarian philosophy. This is in part facilitated through a comparison of Stuart Blackton's Humorous Phases of Funny Faces (1906) – a work directly addressed by Torre, and Emile Cohl's Fantasmagorie (1908) – a work which he largely passes by. It is claimed here that, despite a number of apparent similarities, the animations of Cohl and Blackton express a radically divergent series of ontological commitments. Cohl offers the audience an experience of chaotic, mutable, relational complexity that revels in its incoherence, whilst Blackton presents a series of more straightforward set pieces, dwelling for the most part upon object-centric representational form. The tension between representation and becoming that occurs between these works is employed to facilitate a critical engagement with Torre's process-cognitivism. It is suggested that Torre's work, though exceptional in its pedagogic value, is likewise expressive of this tension, and that in its effort firstly to combine a series of process-philosophical and cognitivist ideas, and secondly to unpack the radical ideas of Deleuze through the more conservative philosophy of Nicholas Rescher, it runs the risk of falling back into a quasi-Kantian philosophy of generality and representation.